2012
DOI: 10.1097/scs.0b013e318241dc53
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Concept for Smart Trepanation

Abstract: Trepanation of the skull is a common procedure in craniofacial and neurosurgical interventions, allowing access to the innermost cranial structures. Despite a careful advancement, injury of the dura mater represents a frequent complication during these cranial openings. The technology of computer-assisted surgery offers different support systems such as navigated tools and surgical robots. This article presents a novel technical approach toward an image- and sensor-based synergistic control of the cutting dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…The micrometric cut of ultrasound vibrations permits a precise, controllable cutting action (Rashad et al 2013), as also confirmed in morphological evaluation by scanning electron microscope study (Bauer & Romanos 2014). Piezosurgery technology works selectively on hard and soft tissues (Bovi et al 2010) and for this reason is frequently used in several bone surgery specialities such as Orthopaedics (Hoign e et al 2011), ENT (Grauvogel et al 2011), Neurosurgery (Follmann et al 2012) and Cranio and Maxillofacial Surgery (Robiony et al 2004).…”
mentioning
confidence: 92%
“…The micrometric cut of ultrasound vibrations permits a precise, controllable cutting action (Rashad et al 2013), as also confirmed in morphological evaluation by scanning electron microscope study (Bauer & Romanos 2014). Piezosurgery technology works selectively on hard and soft tissues (Bovi et al 2010) and for this reason is frequently used in several bone surgery specialities such as Orthopaedics (Hoign e et al 2011), ENT (Grauvogel et al 2011), Neurosurgery (Follmann et al 2012) and Cranio and Maxillofacial Surgery (Robiony et al 2004).…”
mentioning
confidence: 92%
“…Based on the principle of synergistic cooperation, we developed a new concept, the Smart Trepanation System (STS). [6][7][8] It was developed to protect the dura mater and reduce the bone gap without disturbing the existing surgical workflow. The STS instrument is used freehand by the surgeon while automatically adjusting the cutting depth based on a preoperatively acquired computed tomography (CT) data set and the current position relative to the operation site tracked by a standard optical tracking system (►Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The system uses a circular oscillating saw, which has a certain soft tissue preserving capability (2.5 mm) as an additional safety feature to reduce the risk of dural tears to a minimum. 7 The optimized parameter setting of oscillation frequency (10,000 rpm/minute), saw blade thickness (0.5 mm), stroke amplitude (1.5 mm), and saw blade contour was tested at different depths on an artificial skull model using bovine pericardium as a dura equivalent. Up to an overcutting depth of 1.5 mm, no damage occurred, and at a depth of 2.5 mm, only slight perforations at the surface of the pericardium occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Die intrinsisch weichgewebeschonende Eigenschaft des verwendeten Sägeverfahrens kann aufgrund der zirkularen Oszillation jedoch nur für kleine Überstände des Sägeblattes garantiert werden (ca. 2,5 mm) [6]. Hinzu kommt, dass die relevanten Weichgewebe (Hirngewebe oder Blutgefäße) druckempfindlich sind.…”
Section: Introductionunclassified
“…sensorgesteuerten Schnitttiefenregelung, die die Schnitttiefe der Säge durch ein sensorgestütztes automatisches Führungssystem an die jeweiligen ana- tomischen Gegebenheiten anpasst, soll es ermöglicht werden, den Knochen ohne eine Schädigung des darunter liegenden Weichgewebes zu durchtrennen. Die hierfür notwendigen Daten zur Entfernung des Säge-blatts von der unteren Knochen/Weichgewebe-Grenze können durch verschiedenartige Verfahren erfasst werden, beispielsweise Computertomographie, Ultraschall und Licht [4][5][6]. Fokus der in diesem Rahmen vorgenommenen Untersuchungen war die Bestimmung des maximalen Schnitttiefenfehlers dieser drei unterschiedlichen Ansätze in präklinischen Setups [4; 5].…”
Section: Introductionunclassified